MEMAKNAI SELF ESTEEM DENGAN NILAI BUDAYA PASSEMANDARAN DALAM MENCEGAH PERILAKU AUDIT DISFUNGSIONAL - Majid, Jamaluddin (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2022)
Self-esteem is a person's self-confidence that is very decisive about their abilities. The purpose of the study to interpret the behavior of Auditors who have high self-esteem must be based on the value of personal independence because the auditor will have good control in the community. An auditor who has passemandaran culture in itself would be an auditor who has the courage and firmness, but remain prudent in the assignment. The values of passemandaran can be a reference in accepting outside influences and the passemandaran acceptable value as a guide in the fight against unethical behavior especially deviant behavior in the audit assignment. The essence of Passemandaran value is the peak value contained in Ponna Tallu atonganan (three basic policies) consisting of: (1) Mesa Ponge' pallangga (aspect of divinity), (2) Da'duatassisara' (aspects of law and democracy), and (3) Tallu tammalaesang (economic, justice aspect and the aspect of unity).